TRANSMISSION OF TRAUMATIC EXPERIENCE THROUGH FLASHBACK IN THE FILM "SPEAK" - Halimah Kartika Sari; Nungki Heriyati (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2021)
This research entitled ‘Transmission of Traumatic Experience through Flashback in The Film ‘Speak’’ aims to analyze the traumatic experience of Melinda delivered through some flashback illustration as narrative device in film. The method used descriptive analysis to describe the traumatic experience in the film and the data collected is taken the screenshots that categorized based on the Discourse time and Story time in order to show when the flashback occurs. Hence, to analyze the data use Cathy Caruth (1996) examined the experience of trauma is the agony of fear and anxiety that is sometimes difficult to control due to a sudden recall memory in mind and Seymour Chatman (1980) about flashback (retrospection) in film represents the repetition of memory or reviewing the past events or situations. In the discussion found that Melinda as a teenage girl has a mental damage due to the traumatic experience that occurred in the past. The experience is told in the form of flashback that played repetitively in different moment in the film. Thus, the result reveals that the repetition of flashback is used to complement the information and reveal the Melinda’s traumatic experiences which make her could not speak out about the problem sexual violence that occurred to her.